The Effect of Customer Engagement on Loyalty Through Trust and Brand Love for The Toyota Innova Brand in The Tegal City Area - Riyadi, Agus (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study investigates the influence of customer engagement on brand trust, brand love, and brand loyalty for the Toyota Innova brand, focusing on the mediating roles of brand trust and brand love. Background Problems: Understanding the factors that influence brand loyalty is crucial in the competitive automotive industry. Previous research has emphasized the importance of customer engagement, but its impact on brand trust, brand love, and loyalty remains unclear. Research Methods: The research uses a quantitative approach with data collected via an online questionnaire distributed to Toyota Innova consumers in Tegal City, Central Java, using purposive sampling. Data were gathered during November 1–30, 2025, and both primary and secondary data were used for analysis. Finding/Results: The results show that customer engagement significantly impacts brand trust but does not affect brand love. Brand trust enhances brand loyalty, while brand love does not significantly affect loyalty. Additionally, brand trust positively influences brand love, indicating that trust may be the foundation for emotional connection. Conclusion: Customer engagement indirectly influences brand loyalty through brand trust, while brand love does not serve as a significant mediator. This highlights the crucial role of trust in fostering loyalty in the automotive sector.